2021
DOI: 10.1111/bdi.13095
|View full text |Cite
|
Sign up to set email alerts
|

An episode of mania following self‐reported ingestion of psilocybin mushrooms in a woman previously not diagnosed with bipolar disorder: A case report

Abstract: NT is a 21-year-old female identifying woman who came to the office of her outpatient psychiatric provider a month after a hospitalization for a brief psychotic episode, later diagnosed as mania, that she believes was triggered by consuming a substantial amount of psilocybe cubensis mushrooms that she had taken recreationally. While she

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…Although both 10 mg and 25 mg of psilocybin were generally well tolerated by participants in this study, it is important to consider the possible risks. Previous literature, albeit in very rare cases ( Dos Santos et al, 2017 ; Litjens et al, 2014 ; Nichols, 2016 ), has reported a few incidences of serotonin syndrome ( Schifano et al, 2021 ), Hallucinogen Persisting Perception Disorder (HPPD) ( Litjens et al, 2014 ) and substance-related exogenous psychosis ( Hendin and Penn, 2021 ) with psychedelic substances, typically when used recreationally alongside other psychotropic medications. More research including larger, diverse samples are necessary to gain a clearer picture of the acute and longer-term adverse events associated with psilocybin.…”
Section: Discussionmentioning
confidence: 99%
“…Although both 10 mg and 25 mg of psilocybin were generally well tolerated by participants in this study, it is important to consider the possible risks. Previous literature, albeit in very rare cases ( Dos Santos et al, 2017 ; Litjens et al, 2014 ; Nichols, 2016 ), has reported a few incidences of serotonin syndrome ( Schifano et al, 2021 ), Hallucinogen Persisting Perception Disorder (HPPD) ( Litjens et al, 2014 ) and substance-related exogenous psychosis ( Hendin and Penn, 2021 ) with psychedelic substances, typically when used recreationally alongside other psychotropic medications. More research including larger, diverse samples are necessary to gain a clearer picture of the acute and longer-term adverse events associated with psilocybin.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 17 published case studies met all of the selection criteria, five of which involved psilocybin (Barbic et al, 2020;Bickel et al, 2005;Brown et al, 2017;Cohen, 1966;Davies, 1979;Dewhurst, 1980;Dos Santos et al, 2017;Hyde et al, 1978;Lake et al, 1981;Paterson et al, 2015;Perera et al, 1995;Prajapati et al, 2016;Reich and Hepps, 1972;Sami et al, 2015;Szmulewicz et al, 2015;Hendin & Penn, 2021). Table 1 summarizes the case content (each case is numbered) and Table 2 summarizes the themes in each case.…”
Section: Resultsmentioning
confidence: 99%
“…He was hospitalized for four months before his psychosis and manic symptoms remitted. Finally, Case 16 describes a 21-year-old woman who presented to outpatient psychiatry one month following hospitalization related to an episode of mania triggered by psilocybin use (Hendin & Penn, 2021). She reported that while her psilocybin experience was pleasant and "mystical", 36 hours after dosing she experienced irritability, pressured speech, decreased need for sleep, paranoia, and delusions that led her family to contact the police.…”
Section: Resultsmentioning
confidence: 99%
“…One case study of a 21-year-old woman described the occurrence of psychotic mania about 36 h after a single ingestion of psilocybin-containing mushrooms, which could be stabilized first with lithium and aripiprazole, and which was later successfully switched to lamotrigine due to adverse effects. The patient had a positive family history of bipolar disorder (father and paternal grandmother) and was suffering depression and PTSD, but was unmedicated at the time of the episode (Hendin and Penn, 2021 ). Ayahuasca and DMT were also reported to induce mania with psychotic features in patients with bipolar disorder or a positive family history of bipolar disorder.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Further studies will hopefully help to elaborate how populations with diverging attitudes and vulnerabilities may react to these potentially very intense and challenging experiences. This is of particular importance regarding patients with bipolar depression, as classic psychedelics seem to be associated with the induction of manic switches and, in combination with lithium, of epileptic seizures and bad trips (Lake et al, 1981 ; Hendin and Penn, 2021 ; Szmulewicz et al, 2015 ; Viktorin et al, 2014 ). Careful precautions are needed to prevent people from misuse and to establish reliable and professionalized medical procedures for the use of these promising substances.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%